SVPWM zero-sequence voltage elimination for the dual fed common dc-link open-end winding PMSM high-speed starter-generator - Rovere, Luca (2019)
The dual-inverter topology has been widely investigated for Open-End Winding (OEW) machines such as induction motors and Permanent Magnet Synchronous Motors (PMSMs). The extensive work done on this topology showed that three-level inversion can be realized with two two-level inverters connected at each end of the machine terminals. Furthermore the dual-fed OEW topology allows for increased fault-tolerant capability, reduction of the dc-link voltage by half and redundant space-vector combinations. In this PhD work, a dual-inverter made of a Si-based 3ph full-bridge converter and one SiC-based 3ph full-bridge connected across the same dc link has been used to drive an high-speed starter-generator OEW-PMSM for aerospace application. The mixed technology dual-inverter allows to achieve higher system efficiency by exploiting the different nature of the two Voltage Source Converters (VSCs). While on one hand the common dc bus configuration significantly simplifies and reduces the costs of the topology, on the other hand it allows the Zero-Sequence Current (ZSC) to flow freely in the system. Previous work focused on the study of modulations which aim to either reduce or control the average Zero-Sequence Voltage (ZSV) on the controller sample time. The low phase inductance, which characterizes high speed machines implies low Zero-Sequence Impedance (ZSI). Therefore any ZSV applied to the zero-sequence circuit would result in a high frequency, high intensity ZSC ripple with the risk of harming the switching devices. This work presents a novel hybrid Space Vector Pulse Width Modulation (SVPWM) that allows to instantaneously eliminate the ZSV produced by the dual-inverter by square wave modulating the IGBT VSC. The non-sinusoidal machine’s back Electro Magnetic Force (backEMF) has been considered and the effect of the converters Dead Time (DT) on the ZSV has been analysed. Since the ZSV generated by the dual-inverter causes high ZSC to circulate in the machine, the voltage distortion introduced by the DT has been considered as a possible control action to eliminate the ZSC flowing due to the non-sinusoidal machine’s back-EMF. A novel SVPWM for instantaneous ZSV elimination and a zero-sequence DT hysteresis controller have been investigated and experimentally tested both on a scaled-down OEWM and the full-scale high-speed starter-generator prototype.